A roadmap to the successful development and commercialization of microbial pest control products for control of arthropods - Ravensberg, Willem J. (Dordrecht Springer Netherlands, 2011)
Biocontrol is among the most promising methods for a safe, environmentally benign and sustainable crop protection. Microbial pesticides offer a great potential, and it is anticipated that they will become a substantial part of the use of all crop protection products. Their development and commercialization, however, has been difficult and with many failures. For the first time, a rational and structured roadmap has been designed for the development and commercialization of microbial pest control products, based on entomopathogenic bacteria, fungi, viruses and nematodes, for the control of arthropod pests. The emphasis lies on strain screening, product development, up to successful commercialization, from a bio-industry's viewpoint. The building blocks of the entire process are identified. The selection criteria for a microbial pest control agent are defined as well as critical parameters for the development of the product. Implementation of the product into an integrated pest management programme is pivotal for a substantial market uptake. Three phases are distinguished for successful adoption in the market: an appropriate application strategy, an optimal implementation strategy, and an effective adoption strategy. Key success and failure factors are identified. Registration is a major hurdle for biopesticides. Salient registration issues are treated and useful information presented. The road to a successful microbial pest control product is designed. Diagrams illustrate the stepwise approach of the entire process. A future perspective on the biopesticide market is presented with limiting and promotional factors and trends. The significant drivers for success are food safety concern, new research and technology, changes in the regulatory climate, and the occurrence of new invasive pests. This systematic roadmap with a strong focus on economics and market introduction will assist academic researchers and industrial developers of biopesticides in accomplishing their goal: the development of successful cost-effective microbial pesticides.
List of Acronyms and Abbreviations -- Chapter 1. General introduction and outline -- Chapter 2. Selection of a new microbial pest control agent -- Chapter 3. Mass production and product development of a microbial pest control agent -- Chapter 4. Quality control -- Chapter 5. Registration of microbial pest control agents and products and other related regulations. Chapter 6. Implementation of a microbial pest control product in an integrated pest management programme -- Chapter 7. Critical factors in the successful commercialization of microbial pest control products -- Chapter 8. Roadmap to success and future perspective.
Electronic reproduction.
Keywords: Pesticides industry -- Europe; Biological pest control agents industry -- Standards; Arthropod pests -- Biological control -- Environmental aspects; Microbial pesticides -- Safety regulations; Electronic books